Ethno Medicinal Plants Used by the Tharu and Magar Communities of Rupandehi District, Western Nepal - D. Tewari2, Anant Gopal Singh1*, M.P. Panthi1; D. (Current Botany, 2011)
The present research seeks to explore the information of medicinal plants used by local people of Rupandehi district for primary healthcare. Local healers were interviewed regarding the detail uses of plants. A rich and unique diversity of 74 ethno medicinal plant species belonging to 45 families under 64 genera were documented. The use of plants In Rupandehi is an old tradition and the exploration of such unique cultures should be completed thoroughly so that the oral traditions are not lost forever. Immediate conservation and management approaches of valuable medicinal plants with the involvement of local indigenous people of Rupandehi district will encourage the sustainable conservation of both biological and cultural diversity